PROBLEMS AND SOLUTIONS OF TEACHING MODERN PHYSICS IN HIGHER EDUCATION - N.Z.Mamadaliyeva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation.  The  article  analyzes  the  issues  of  what  new  courses  should  be introduced as a special subject for bachelors, masters and students of retraining and advanced training courses for teachers in the "Physics" training direction, the scope of teaching  the  selected  subjects,  what  criteria  should  be  used  in  their  selection,  its naming, in particular, the term "modern physics", its content - essence and differences from "classical" physics, theoretical analyses and solutions, as well as some current issues of teaching modern physics as a special elective subject.